2020
DOI: 10.1016/j.placenta.2020.08.015
|View full text |Cite
|
Sign up to set email alerts
|

Consistent localization of SARS-CoV-2 spike glycoprotein and ACE2 over TMPRSS2 predominance in placental villi of 15 COVID-19 positive maternal-fetal dyads

Abstract: Introduction While the COVID-19 pandemic continues to have a significant global health impact, rates of maternal to infant vertical transmission remain low (<5%). Parenchymal changes of placentas from COVID-19 infected mothers have been reported by several groups, but the localization and relative abundance of SARS-CoV-2 viral proteins and cellular entry machinery has not been fully characterized within larger placental tissue cohorts. Methods An extended placental tiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
162
1
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 124 publications
(185 citation statements)
references
References 41 publications
18
162
1
4
Order By: Relevance
“…A higher frequency of maternal vascular malperfusion (MVM) of the placental bed was reported in placentas of pregnant women infected with SARS-CoV-2 by 13 studies [ 16 , 22 , 23 , 25 , 27 , 28 , 31 , 32 , 38 , 40 , 42 , 43 , 44 ]. It is a recognized pattern of placental injury related to abnormal uterine perfusion, leading to a myriad of pathological changes such as accelerated villous maturation, increased perivillous and intervillous fibrin deposition, decidual vasculopathy, Tenney–Parker change, villous infarction, and intervillous thrombosis [ 75 ].…”
Section: Placental Morphological Changesmentioning
confidence: 99%
See 4 more Smart Citations
“…A higher frequency of maternal vascular malperfusion (MVM) of the placental bed was reported in placentas of pregnant women infected with SARS-CoV-2 by 13 studies [ 16 , 22 , 23 , 25 , 27 , 28 , 31 , 32 , 38 , 40 , 42 , 43 , 44 ]. It is a recognized pattern of placental injury related to abnormal uterine perfusion, leading to a myriad of pathological changes such as accelerated villous maturation, increased perivillous and intervillous fibrin deposition, decidual vasculopathy, Tenney–Parker change, villous infarction, and intervillous thrombosis [ 75 ].…”
Section: Placental Morphological Changesmentioning
confidence: 99%
“…Maternal hypoxia secondary to severe COVID-19 lung infection may initiate uterine underperfusion and subsequent hypoxic-ischemic injury to the placenta. Taglauer et al (2020) reported that 14 of the 15 (93%) third trimester placentas revealed at least a feature of MVM, with infarcts and increased fibrin deposition being the most frequently observed, compared to healthy controls where MVM was observed only in 30% (3/10) of cases [ 42 ]. This was similar with that reported by Zhang et al (2020) and Hecht et al (2020) [ 25 , 44 ], although their findings did not meet statistical significance.…”
Section: Placental Morphological Changesmentioning
confidence: 99%
See 3 more Smart Citations